Exacerbation of working conditions due to the economic pressures of hospitals: Mandatory staffing ratios for physicians? Verschärfung der Arbeitsbedingungen durch Kostendruck der Krankenhäuser: Verpflichtende Personalschlüssel für Ärzte? - Bellut, Laura; Faßbach, M.; Schroeder, A.; Westphal, J.; Beck, A. (Urologe, 2021)
Background: In current hospital-based urological care, economic pressure and its influence on urological working and further training conditions are a main point of criticism among young urologists. Against the background of a growing need for young talent in our specialist discipline, there is an urgent need for action. With the introduction of the lower limits for nursing staff, there is now a threat of a reduction in the number of physicians with the aim of reducing costs for business reasons. Objective: A mandatory staffing ratio is often mentioned to counteract the downsizing in German clinics. The role of the lower staffing limit is explained in the following article. Materials and methods: We have analyzed the current draft laws of the federal government, as well as position papers and statements from federal political representatives such as the Marburger Bund, Bundesverband Deutscher Urologen and the German Medical Association (Bundesärztekammer) since 2018. Results and conclusion: The analysis of current developments in nursing policy shows that the first step is a needs-based assessment of personnel and subsequent financing in the clinic setting. With adequate staffing, as in the traffic light scheme of the German Medical Association, not only would clinics position themselves as attractive employers and training centers for large parts of the urological medical profession, but would also significantly improve working conditions, patient care and patient safety. Medical training must remain an essential part of everyday hospital life.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Burnout; Diagnosis related groups; Medical residency; Specialist training; Work-life balance